Ab initio Modelling of Plasmons in Metal‐semiconductor Bilayer Transition‐metal Dichalcogenide Heterostructures. Issue 6 (24th January 2017) - Sen, Huseyin Sener; Xian, Lede; H. da Jornada, Felipe; Louie, Steven G.; Rubio, Angel
Abstract: Two‐dimensional transition‐metal dichalcogenides (TMDs) have attracted enormous interest, due to the richness of their optical and electronic properties. Here, we consider two prototypical two‐dimensional TMD metal‐semiconductor bilayer heterostructures, VSe2 ‐MoSe2 and VSe2 ‐WSe2, and investigate the effect of the semiconducting layer on the plasmons supported by the metallic layer using first principles time‐dependent density functional theory (TDDFT) calculations. We focus on the flat region of the plasmon dispersion, where momentum transfer is larger than 0.05 Å −1 and the interband transitions gain importance. With the addition of the semiconducting layer, we show that the electronic band structure undergoes significant changes close to the Fermi level, and hybridization occurs, which leads to strengthening of the interband transitions and a significant redshift in the plasmon energy. Abstract :